2020
DOI: 10.1051/e3sconf/202019701005
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Indirect Integration of Steam Rankine Cycles in Concentrated Solar Power Coupled with Thermochemical Storage

Abstract: Storing energy in thermo-chemical form is a promising alternative for renewable energy sources and one of the fields that could exploit its advantages is constituted by Concentrated Solar Power (CSP). High efficiencies, high energy densities, long-term storage and dispatchability in power generation could be tackled with the employment of a Calcium-Looping in a central tower CSP plant. Although Brayton cycles based on sCO2 and He probably represent the most efficient option, it can be interesting to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Karasavvas et al [65] integrated the Rankine cycle with the CO 2 Brayton cycle heat storage system and designed a scheme of continuous power generation with an efficiency of 31.5%. Tesio et al [66] optimized the indirect integration of the steam Rankine cycle in CaL-CSP from both energy and economic aspects, which determined the size and operating conditions of the main components. Ortiz et al [67] conducted an energy and sensitivity analysis on the closed system, and the results showed that various methods could be used to improve the system efficiency by adding gas-solid heat exchangers at both ends of the calciner and carbonator, increasing the turbine inlet temperature, and raising CaO conversion.…”
Section: Csp-cal Schemesmentioning
confidence: 99%
“…Karasavvas et al [65] integrated the Rankine cycle with the CO 2 Brayton cycle heat storage system and designed a scheme of continuous power generation with an efficiency of 31.5%. Tesio et al [66] optimized the indirect integration of the steam Rankine cycle in CaL-CSP from both energy and economic aspects, which determined the size and operating conditions of the main components. Ortiz et al [67] conducted an energy and sensitivity analysis on the closed system, and the results showed that various methods could be used to improve the system efficiency by adding gas-solid heat exchangers at both ends of the calciner and carbonator, increasing the turbine inlet temperature, and raising CaO conversion.…”
Section: Csp-cal Schemesmentioning
confidence: 99%